Nonmotor symptoms evolution during 24 months of bilateral subthalamic stimulation in Parkinson's disease. Issue 3 (21st February 2018) - Dafsari, Haidar S.; Silverdale, Monty; Strack, Marian; Rizos, Alexandra; Ashkan, Keyoumars; Mahlstedt, Picabo; Sachse, Lena; Steffen, Julia; Dembek, Till A.; Visser‐Vandewalle, Veerle; Evans, Julian; Antonini, Angelo; et al.
Abstract: Background: The objective of this study was to investigate 24‐month of effects of bilateral subthalamic nucleus (STN) deep brain stimulation (DBS) on nonmotor symptoms in Parkinson's disease (PD). Methods: In this prospective, observational, multicenter, international study including 67 PD patients undergoing bilateral STN‐DBS, we examined the Non‐motor Symptom Scale, Non‐Motor Symptoms Questionnaire, Parkinson's Disease Questionnaire‐8, Scales for Outcomes in Parkinson's Disease‐motor examination, ‐activities of daily living, and ‐complications, and levodopa‐equivalent daily dose preoperatively and at 5 and 24‐month of follow‐up. After checking distribution normality, longitudinal outcome changes were investigated with Friedman tests or repeated‐measures analysis of variance and Bonferroni correction for multiple comparisons using multiple tests. Post hoc, Wilcoxon signed rank t tests were computed to compare visits. The strength of clinical responses was analyzed using effect size. Explorative Spearman correlations of change scores from baseline to 24‐month follow‐up were calculated for all outcomes. Results: The Non‐motor Symptom Scale and all other outcome parameters significantly improved from baseline to the 5‐month follow‐up. From 5 to 24‐month, partial decrements in these gains were found. Nonetheless, comparing baseline with 24‐month follow‐up, significant improvements were observed for the Non‐motor Symptom Scale (small effect), Scales for Outcomes in PD‐motor examination showed a moderate effect, and Scales for Outcomes in Parkinson's Disease‐complications and levodopa‐equivalent daily dose showed large effects. Non‐motor Symptom Scale change scores from baseline to 24‐month follow‐up correlated significantly with Parkinson's Disease Questionnaire‐8, Scales for Outcomes in Parkinson's Disease‐activities of daily living, and ‐motor complications change scores. Conclusions: This study provides evidence of beneficial effects of bilateral STN‐DBS on nonmotor symptoms at 24‐month follow‐up. The extent of nonmotor symptom improvement was directly proportionate to improvements in quality of life, activities of daily living, and motor complications. This study underlines the importance of nonmotor symptoms for holistic assessments of DBS outcomes. © 2018 International Parkinson and Movement Disorder Society